Optimizing reinforced concrete beams cost based on AI-based Lagrange functions - Won-Kee Hong; Van Tien Nguyen; Manh Cuong Nguyen (Journal of Asian Architecture and Building Engineering)
This study aims to develop artificial neural networks (ANNs)-based forward Lagrange networks optimizing ductile doubly reinforced concrete (RC) beams. Cost (CIb) of materials and manufacture were established as an objective function, which is minimized considering constraints according to engineer’s needs. Large datasets of 100,000 were used to derive an AI-based objective function for cost (CIb, minimizing cost of an RC beams) as a function of forward input parameters, replacing complex analytical objective functions. A resilient design capable of finding concrete beams beyond human efficiency is based on equality and inequality constraints, which are implanted in AI-based Lagrange. Optimal designs are not simple especially when multiple constraining conditions are to be considered. Neither is it possible for engineers to pre-assign constraining conditions which can be sequentially calculated in an output of a conventional design. Cost of RC beams minimized by forward Lagrange networks was reduced 18%–26% compared to probable beam designs. AI-based design charts with eight forward outputs (ϕMn,Mu,Mcr,εrt_0.003,εrc_0.003,Δimme,Δlong,CIb) based on nine forward inputs (L, h, b, fy,f’c, ρrt,ρrc,MD,ML) are proposed to assist engineers to design ductile doubly RC beams, presenting minimized CIb in the preliminary design stage.